The role of religiosity on relationship between chronic health problems and psychological well-being among Malay Muslim older persons. - Momtaz, Yadollah Abolfathi; Tengku Abdul Hamid, Tengku Aizan; Yahaya, Nurizan (Medwell Publishing, 2009)
It is recognized that religiosity contributes to psychological well-being of older persons, however, effects of religiosity on psychological well-being older person with chronic health problems is lacking. This study aimed to examine the mediating effect of religiosity on the relationship between chronic health problems and psychological well being among Malay Muslim older persons aged 60 years and over. Data for this study came from the national survey (PSRPWO) that employed a cross-sectional research design conducted from 2007 until 2008 in Peninsular Malaysia. Religiosity, psychological well being and morbidity were measured using intrinsic/extrinsic revised scale, WHO-5 well-being index and a checklist of 16 chronic health problems, respectively. In this study, the reliability test for WHO-5 Well-Being Index revealed 0.84 Cronbach's α and 0.85 for the religiosity scale. Out of 1415 subjects examined in this study 51.0% were female and 49.0% male. The mean score for religiosity found 47.1 (SD = 5.87). The mean of psychological well being was 62.36 (SD = 22.47).The mean number of chronic health problems computed was 1.3 (SD = 1.33). The results of multiple regression analysis and Sobel-test (t = -2.61, p<0.01) indicated that relationship between chronic health problems and psychological well being is significantly moderated by religiosity. This study implies that religiosity is an important resource in improving psychological well being of older persons with chronic health problems.